2017
DOI: 10.1016/j.jbiomech.2017.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of knee joint models used in multi-body kinematics optimisation for soft tissue artefact compensation

Abstract: Estimating joint kinematics from skin-marker trajectories recorded using stereophotogrammetry is complicated by soft tissue artefact (STA), an inexorable source of error. One solution is to use a bone pose estimator based on multi-body kinematics optimisation (MKO) embedding joint constraints to compensate for STA. However, there is some debate over the effectiveness of this method. The present study aimed to quantitatively assess the degree of agreement between reference (i.e., artefact-free) knee joint kinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…However, except for spherical and hinge type models, other existing joint model designs require precise geometry of bone, articulation, and ligaments [24,25,28]. In addition, a previous report suggested that the best joint model type may be motor task-dependent [27]. A thorough assessment of MKO embedding more complex joint models is warranted for a better description of pelvic limb kinematics during canine gait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, except for spherical and hinge type models, other existing joint model designs require precise geometry of bone, articulation, and ligaments [24,25,28]. In addition, a previous report suggested that the best joint model type may be motor task-dependent [27]. A thorough assessment of MKO embedding more complex joint models is warranted for a better description of pelvic limb kinematics during canine gait.…”
Section: Discussionmentioning
confidence: 99%
“…MKO was introduced to provide another STA-compensated solution for the estimation of 3-D kinematics of the pelvic limb by minimizing the differences between model-determined and measured skin marker coordinates using a global optimization strategy [22,23]. The MKO approach and its modifications have been widely assessed for their STA compensation capability in human gait analysis [23][24][25][26][27][28]. MKO offers the advantage that it can be implemented with conventional 3-D marker sets and therefore could provide a possible alternative for STA compensation in canine motion analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact is that human skeletal structures are not exposed to the outside environment but are surrounded by the soft tissues (the muscles, the fat, the skin, etc.). Therefore, an effective measuring technique that could directly or indirectly detect the motion of the bone is necessary to monitor and trace the movements of bone segments underlying the skin surface [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of STA to knee joint kinematics has been reported to lead to average rotational errors of up to 4.4 • and 13.1 • and average translational errors of up to 13.0 mm and 16.1 mm for walking and cutting motions, respectively [17]. Although many researchers attempted to compensate for the STA by computer modeling [13,[18][19][20][21][22][23][24], no significant improvement has been found in previous studies [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent special edition of the Journal of Biomechanics proposed new and innovative techniques to mitigate some of the effects of softtissue artifact [2]. While these techniques improve the overall fidelity of motion capture data, they introduce new challenges to both the collection and processing workflows [3][4][5][6][7]. This study takes a different approach to the problem; instead, seeking to understand how currently implemented techniques can be streamlined to preserve tolerable fidelity compared to unconstrained-kinematic models while reducing the burdens placed on subjects and researchers.…”
Section: Introductionmentioning
confidence: 99%